An experimental investigation of optimal learning in coordination games - Andreas Blume; Uri Gneezy (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
This paper presents an experimental investigation of optimal learning in repeated coordination games. We find evidence for such learning when we limit both the cognitive demands on players and the information available to them. We also find that uniqueness of the optimal strategy is no guarantee for it to be used. Optimal learning can be impeded by both irrelevant information and the complexity of the coordination task. – – In diesem Beitrag wird eine experimentelle Untersuchung des optimalen Lernens in wiederholten Koordinationsspielen vorgestellt. Derartiges Lernen wird beobachtet, wenn kognitive Anforderungen an die Spieler und die ihnen zur Verfügung stehende Information begrenzt sind. Es zeigt sich aber auch, daß die Einzigartigkeit der optimalen Strategie keine Garantie dafür ist, daß sie angewendet wird. Optimales Lernen kann sowohl durch irrelevante Informationen als auch durch die Komplexität der Koordinationsaufgabe behindert werden.
Keywords: 330